2020
DOI: 10.1002/cnr2.1274
|View full text |Cite
|
Sign up to set email alerts
|

HER2‐positive breast cancer brain metastasis: A new and exciting landscape

Abstract: Background: Brain metastases (BrM) incidence is 25% to 50% in women with advanced human epidermal growth factor receptor 2 (HER2)-positive breast cancer. Radiation and surgery are currently the main local treatment approaches for central nervous system (CNS) metastases. Systemic anti-HER2 therapy following a diagnosis of BrM improves outcomes. Previous preclinical data has helped elucidate HER2 brain trophism, the blood-brain/blood-tumor barrier(s), and the brain tumor microenvironment, all of which can lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 125 publications
(294 reference statements)
1
54
0
1
Order By: Relevance
“…Moreover, the survival of these patients is generally poor, and the median overall survival (OS) after the initial diagnosis of CNS metastases is 13.0 months 6 . Although anti-HER2 therapeutic options have steadily enhanced the effect of systemic therapy on patients with HER2+ metastatic breast cancer (MBC), there is an increased awareness that clinical strategies targeting BM are needed for this subtype of BC 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the survival of these patients is generally poor, and the median overall survival (OS) after the initial diagnosis of CNS metastases is 13.0 months 6 . Although anti-HER2 therapeutic options have steadily enhanced the effect of systemic therapy on patients with HER2+ metastatic breast cancer (MBC), there is an increased awareness that clinical strategies targeting BM are needed for this subtype of BC 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages, like monocytes, can cross the BBB and may be able to infiltrate the tumor. Brain metastasis is prevalent in subtypes (triple-negative and HER2 þ ) of breast cancer (Zimmer et al, 2020;Lv et al, 2021). Choi et al first reported that macrophages-mediated delivery of nanoparticles for brain delivery.…”
Section: Leukocytes-based Vehicles For Brain Tumor Drug Deliverymentioning
confidence: 99%
“…Brain metastases are common in patients with HER2positive mBC; it is estimated that brain metastases will ultimately develop in 25-50% of female patients [32]. Even after treatment with whole brain radiotherapy, brain metastases have a negative impact on patients' quality of life and outcome [33], highlighting the need for more effective treatments.…”
Section: Unmet Needsmentioning
confidence: 99%
“…Even after treatment with whole brain radiotherapy, brain metastases have a negative impact on patients' quality of life and outcome [33], highlighting the need for more effective treatments. Trastuzumab has low central nervous system penetrance and is not effective at treating brain metastases compared with HER2-targeted therapies in development, such as tucatinib [32,[34][35][36]. Long-term follow-up of patients with HER2-positive CRC treated with trastuzumab and lapatinib also showed the central nervous system to be a 'sanctuary site' of relapse [37,38].…”
Section: Unmet Needsmentioning
confidence: 99%